AGREEMENT RE COMPENSATION OF EMPLOYER‘S EXPENSES FOR THE TRAINING OF THE EMPLOYEE - Povilaitienė, Ieva (Teisė, 2017)
This article briefly analyzes legal nature of additional agreements, concluded between the employer and the employee, and, in order to illustrate the topic, it views one of the most popular kinds of such agreements met in recent practice of Lithuania. Respective case-law of the Lithuanian Supreme Court is also analyzed in this article, as well as essential problems and issues rising regarding the content of such agreements and regarding implementation of rights and duties of the parties related to implementation of such agreements.